2015
DOI: 10.1007/s10750-015-2495-7
|View full text |Cite
|
Sign up to set email alerts
|

Past, present, and future roles of small cladoceran Bosmina longirostris (O. F. Müller, 1785) in aquatic ecosystems

Abstract: Bosmina longirostris is a small-bodied, filter-feeding cladoceran. The species is widely distributed throughout the world in temperate and tropical climates, where it persists in all kinds of freshwater bodies regardless of their trophy, acidification, or salinity. Its wide distribution causes B. longirostris to be one of the most taxonomically recognizable Cladocera species all over the world, despite the fact that the species is a well-known example of a taxon with confused taxonomy. Although B. longirostris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 88 publications
1
16
0
Order By: Relevance
“…These observations support the contention that bosminids feed well on small-bodied prey (Adamczuk, 2016). For example, the peaks in phytoplankton in the macrophyte absent ponds by two different dominant taxa over the course of time can also be explained in reference to the shifts in the zooplankton assemblages.…”
Section: Macrophytes Affect Phytoplankton Assemblage Structuresupporting
confidence: 82%
“…These observations support the contention that bosminids feed well on small-bodied prey (Adamczuk, 2016). For example, the peaks in phytoplankton in the macrophyte absent ponds by two different dominant taxa over the course of time can also be explained in reference to the shifts in the zooplankton assemblages.…”
Section: Macrophytes Affect Phytoplankton Assemblage Structuresupporting
confidence: 82%
“…D. magna is able to minimize the food stress caused by the filamentous cyanobacteria by setae thickening [74]. Although B. longirostris is common species in cyanobacterial blooms [81], it is probably unable to compete with such a large cladoceran species as D. magna.…”
Section: Species Composition and Quantitative Variablesmentioning
confidence: 99%
“…Some cladocerans, such as B. fatalis , may be relicts with restricted-range (endemic), whereas others, commonly and widely distributed within their extensive primary ranges, possiblely are not [2]. We found close relatives among B. longirostris lineages from China, Denmark, Germany, Russia, Japan and the USA, which suggested that B. longirostris is widespread in the Holarctic region [42]. Therefore, B. longirostris should be an advanced lineage and have a non-relict status, which affected by current climate [43].…”
Section: Discussionmentioning
confidence: 96%